The Effect of Nitric Oxide Donor in Diabetic Wound Healing - N Dashti; M Ansari; M Shabani; S Vardasti; A Mirsalehian; MH Noori Mughehi; ZN Hatmi (Tehran University of Medical Sciences, 2003)
Diabetes is characterized by a nitric oxide deficiency at the wound site. Diabetes is a factor that influences all stages of wound healing. In animals with acute experimental diabetes induced by streptozotocin (STZ), the early inflammatory responses after wounding is impaired, fibroblast and endothelial cell proliferation is reduced as well as accumulation of reparative collagen and gain in wound breaking strenght. This study investigated whether exogenous nitric oxide supplimentation with nitric oxide donor DETA NONOate could reverse impaired healing in diabetes. The results suggest nitric oxide donor DETA NONOate can reverse impaired healing associated with diabetes (P